Unrecorded alcohol and alcohol-related harm in rural Sabah, Malaysia: a socio-economically deprived region with expensive beer and cheap local spirits - Wendy Shoesmith; Naing Oo Tha; Daw Khin Saw Naing; Ahmad Faris Abdullah; Roslee Abbas (2016)
To investigate recorded and unrecorded alcohol and the relation to alcohol-related harm in a region with high taxation, economic deprivation and cultural use of alcohol. Methods: Two participants per household were systematically sampled from 12 different villages chosen using stratified random sampling in the North of Sabah, Malaysia. Participants were asked about each type and amount of drink consumed; price paid, whether tax was paid, number of days sick in the last year and whether they had experienced various health problems. A brief screen for mental disorders (PHQ) and an alcohol disorder screening test (AUDIT) were completed. Village heads were also interviewed about alcohol-related problems at village level. Results: 470 people were interviewed. The most commonly drunk beverages were beer and Montoku (a local distilled beverage), which had average prices of RM3.85 and RM0.48 per standard drink respectively. Montoku was more likely to be drunk by problem drinkers. Only 3.1% of alcohol drunk was believed by respondents to be taxed. Men with an AUDIT score of more than 15 were more likely to have had a sick day in the last year and have a female household member with symptoms of mental disorder on PHQ. Conclusions: Change in the taxation structure needs to be considered to reduce alcohol-related harm. Most alcohol consumed in rural Sabah is smuggled or informal. The low price of local spirits is likely to be contributing to alcohol-related harm. Differential effects on minority populations need to be considered when designing alcohol policy.